Effect of Ti particle size on mechanical and tribological properties of TiCN coatings prepared by reactive plasma spraying. Issue 18 (15th December 2017) - Qin, Yanfang; He, Jining; Yin, Fuxing; Liu, Baoxi; Zhang, Fanyong
Abstract: Titanium carbonitride (TiCN) coatings were successfully fabricated by reactive plasma spraying (RPS) from agglomerated Ti-graphite feedstock. The effect of Ti particle size on the microstructure and phase composition of plasma sprayed TiCN coatings was investigated. The Vickers microhardness of coatings was measured by a Microhardness Test and the corresponding Weibull distribution were also analyzed. In addition, a pin-on-disk tribometer was employed to determine the trobological properties of coatings. Results show that all the coatings consist of TiC x N 1−x (0 ≤ x ≤1) and minor Ti2 O phases, and the amount of Ti2 O increases with the increase of Ti particle size. The Weibull distribution of Vickers microhardness of all the coatings shows apparent scattering, while the coating sprayed with Ti particle size of 28 µm exhibits a relatively even distribution. Compared with the coating sprayed with Ti particle size of 14 µm or 48 µm, the coating sprayed with Ti particle size of 28 µm exhibits improved mechanical and tribological properties, which are attributed to the high microhardness and strong bonding strength. Highlights: All the coatings consist of TiC x N 1-x (0 ≤ x ≤1) and minor Ti2 O phases. The coating sprayed with coarse Ti particle size present rough surface morphology. The coating sprayed with Ti particle size of 28 μm possesses improved performances. The wear mechanism is abrasive wear accompanied with tribo-oxidation wear.